A Lifespan Perspective on Entrepreneurship: Perceived Opportunities and Skills Explain the Negative Association between Age and Entrepreneurial Activity - Bohlmann, Clarissa; Rauch, Andreas; Zacher, Hannes (Frontiers in Psychology, 2017)
Researchers and practitioners are increasingly interested in entrepreneurship as a means to fight youth unemployment and to improve financial stability at higher ages. However, only few studies so far have examined the association between age and entrepreneurial activity. Based on theories from the lifespan psychology literature and entrepreneurship, we develop and test a model in which perceived opportunities and skills explain the relationship between age and entrepreneurial activity. We analyzed data from the 2013 Global Entrepreneurship Monitor (GEM), while controlling for gender and potential variation between countries. Results showed that age related negatively to entrepreneurial activity, and that perceived opportunities and skills for entrepreneurship mediated this relationship. Overall, these findings suggest that entrepreneurship research should treat age as a substantial variable.